Explaining and forecasting euro area exports: which competitiveness indicator performs best? - Michele Ca' Zorzi; Bernd Schnatz (European Central Bank (ECB), 2007)
From a conceptual point of view there is little consensus of what should be the “ideal indicator” of international cost and price competitiveness as each of the standard measures typically employed has its own merits and drawbacks. This calls for addressing the question from an empirical angle, searching for the indicator that best explains and helps forecast export developments. This paper constitutes a first attempt to systematically compare the properties of the alternative cost and price competitiveness measures of the euro area. Although they diverge sometimes, we find little evidence that there is one indicator consistently outperforming the other in terms of explaining and forecasting euro area exports. This suggests that the measures based on consumer and producer prices, which offer some advantages in terms of quality and timeliness, are good approximations of euro area price and cost competitiveness.
Keywords: F17; F31; F41; 330; euro area; exports; forecast; price competitiveness; real exchange rate; Trade; Kaufkraftparität; Außenhandelspreis; Internationaler Wettbewerb; Preiswettbewerb; Produktionskosten; Eurozone; Wirtschaftsindikator